Behavior of Primary Human Oral Keratinocytes Grown on Invisalign® SmartTrack® Material - Michael Nemec; Hans Magnus Bartholomaeus; Christian Wehner; Christian Behm; Hassan Ali Shokoohi-Tabrizi; Xiaohui Rausch-Fan; Oleh Andrukhov; Erwin Jonke (Applied Sciences, 2021)
Orthodontic clear aligner treatment is gaining tremendous popularity. The world market leader is Align Technology® and its product Invisalign®. Although numerous patients are treated with Invisalign® aligners, only little is known about the cellular effects of aligner material on oral epithelial cells. In the present study, we aimed to investigate the effects of SmartTrack® clear aligner material on directly cultured primary human oral keratinocytes (HOKs). Cell morphology and behavior were investigated by scanning electron microscopy and bright field microscopy. Aligner effects on viability were detected by cell-counting-kit (CCK)-8 and live/dead staining. Gene expression of several inflammatory and barrier proteins was assessed by qPCR. Cells cultured on tissue culture plastic served as control. Cell proliferation/viability was significantly lower in cells cultured on aligner material (p < 0.05) in comparison to control. Live/dead staining did not reveal an increase in the number of dead cells on aligner surfaces. After two and seven days of incubation, interleukin (IL)-6 expression decreased, and IL-8 expression increased in HOKs cultured on aligner surfaces. The expression of intercellular adhesion molecule 1 (ICAM-1) significantly decreased after seven days. Gene expression of epithelial barrier markers showed that integrin (ITG)-α6 significantly decreased after two and seven days. A significant decrease in ITG-β4 and E-cadherin expression levels compared to control could only be seen after seven days. We did not find any cytotoxic effect, but alterations in the cell’s barrier functions and inflammatory reaction were obvious. Clinical studies are required to give further insights into clinical reactions on the underlying aligner material of this quickly expanding orthodontic appliance.